Antioxidative Properties ff White Saffron Extract (Curcuma mangga Val.) In The In Vivo Assay - Dwiyati Pujimulyani; Agung Wayzka; Sri Anggrahini; Umar Santoso (Faculty of Agricultural Technology, Universitas Gadjah Mada, Yogyakarta, Indonesia, 2012)
A study on the antioxidative properties of white saffron extract (in vivo) has been conducted. The purpose of this study was to determine the antioxidative effects of white saffron extract in in vivo assay. Fresh white saffrons were peeled, washed, blanched at 100˚C in 0.5% citric acid solution for 5 minutes and grated. The ratio between grated white saffron and distilled water was 1:1; 1:2; 1:3 and 1:4. Then it was filtered in order to obtain white saffron extract. The extract was evaluated in terms of its antioxidant activity by using in vivo. Five-week old male Wistar rats were purchased from Experimental Animal Development Unit, Gadjah Mada University. After one week of adaptation, the rats were divided into six groups, feed and drinking water were provided ad libitum. White saffron extract was orally administrated using a syringe at 09.00 a.m and 14.00 p.m daily, for 14 days. The livers and serum were removed for analysis of thiobarbituric acid reactive subtances (TBARS), α-tocopherols and superoxide dismutase (SOD). The results of this study showed that white saffron extract has an antioxidative activity in the in vivo assay. The higher concentration of white saffron extract, the higher α-tocopherols and superoxide dismutase, but the TBARS value was lower.